Consensus on glass-ionomer cement thresholds for restorative indications - Lima Navarro, Maria Fidela de; Pascotto, Renata Correa; Sanches Borges, Ana Flavia; Soares, Carlos Jose; Raggio, Daniela Procida; Rios, Daniela; Bresciani, Eduardo [UNESP]; Molina, Gustavo Fabian; Hien Chi Ngo; Miletic, Ivana; Frencken, Jo; Wang, Linda; et al. (Elsevier B.V., 2021)
Objective: The aim of this paper is to present the results of a consensus meeting on the threshold property requirements for the clinical use of conventional glass-ionomer cements (GICs) for restorative indications. Methods: Twenty-one experts on GICs evaluated the results of tests on mechanical and optical properties of 18 different brands of restorative GICs: Bioglass R [B], Chemfil Rock [CR], Equia Forte [EF], Gold Label 2 [GL2], Gold Label 9 [GL9], Glass Ionomer Cement II [GI], Ionglass [IG], Ion Z [IZ], Ionomaster [IM], Ionofil Plus [IP], Ionostar Plus [IS], Ketac Molar Easymix [KM], Magic Glass [MG], Maxxion R [MA], Riva Self Cure [R], Vidrion R [V], Vitro Fil [VF] and Vitro Molar [VM]. All experiments were carried out by a team of researchers from Brazil and England following strict protocols, under the same laboratory conditions throughout, and maintaining data integrity. Results: There was consensus on: determining as primary properties of the material: compressive strength, microhardness, acid erosion and fluoride release, and as secondary properties: contrast ratio and translucency parameter, in order to rank the materials. Seven brands were below the thresholds for restorative indications: IZ, IM, IG, MA, VF, B and MG. Conclusions: Based on the primary properties adopted as being essential for restorative indications, the conventional restorative GICs that met the thresholds and could be considered suitable as long-term restorative materials were: EF, GI, GL9, KM, IP, GL2, IS, CR, V, VM and R. A decision-making process to select the best GIC must also include results from clinical trials. Clinical significance: This study provides a ranking of GICs that could be considered suitable as long-term restorative materials based on their main properties.
Keywords: Glass-ionomer cements; Biomaterial(s); Biomechanics; Cement; Clinical practice guidelines